Potency Study of N-Hexane Extracts of Black Plum (Syzygium cumini (L.) Skeels) in the Inhibitation Growth of Salmonella typhi and Candida sp. - Saida Rasnovi; Risa Nursanty (Universitas Syiah Kuala, 2014)
N-hexane extracts of the bark from black plum (Syzygium cumini (L.) Skeels) showed activity against Salmonella typhi. Meanwhile, the result showed that N-hexane was not able to inhibit the growth of Candida sp. The research was done at Microbiology laboratory, Biology Department Faculty of Mathematics and Science, Syiah Kuala University. The barks of black plum were collected from Aceh Besar District. The extraction method for black plum used maceration with N-hexane and than concentrated in rotary evaporator. The disc diffusion method used to screen the antimicrobial activity with 20 %, 30 %, 40 % dan 50 % concentration.